2020
DOI: 10.14336/ad.2019.0724
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Xist Regulates Osteoblast Differentiation by Sponging miR-19a-3p in Aging-induced Osteoporosis

Abstract: The switch between osteogenic and adipogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) plays a key role in aging-induced osteoporosis. In this study, miR-19a-3p was obviously downregulated in BMSCs from aged humans and mice. Overexpressed miR-19a-3p evidently reduced aginginduced bone loss in mice and promoted osteogenic differentiation of BMSCs, while silenced miR-19a-3p manifestly increased aging-induced bone loss in mice and repressed osteogenic differentiation of BMSCs. Hoxa5 was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Elevated miR-19a-3p expression is associated with the potential of lymph node metastasis ( 34 , 35 ). Moreover, recent study highlighted the positive role of miR-19a-3p in osteoblast differentiation by targeting Hoxa5 ( 36 ). However, the role of miR-19a-3p in osteoclastogenesis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated miR-19a-3p expression is associated with the potential of lymph node metastasis ( 34 , 35 ). Moreover, recent study highlighted the positive role of miR-19a-3p in osteoblast differentiation by targeting Hoxa5 ( 36 ). However, the role of miR-19a-3p in osteoclastogenesis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…eskildsen et al (11) showed that mirna-138 was related to the osteogenic differentiation of hMScs and that the overexpression of mir-138 inhibited the oB differentiation of hMScs. The lncrna Xist was found to sponge mir-19a-3p to repress BMSc osteogenic differentiation in ageing-induced osteoporosis (12). owing to the development of deep sequencing technology, an increasing number of biologically significant ncRNAs affecting bone metabolism and osteoporosis have been studied.…”
Section: Effects Of Mirnas Lncrnas and Circrnas On Osteoporosis As Regulatory Factors Of Bone Homeostasis (Review)mentioning
confidence: 99%
“…The switch between the adipogenic and osteogenic differentiation of BMScs plays an important role in ageing-induced osteoporosis. mir-19a-3p is able to regulate oB differentiation in BMScs by regulating Hoxa5 expression, and lncrna Xist, as a sponge of mir-19a-3p, plays a crucial role in oB differentiation by binding mir-19a-3p in BMScs (12). recently, Zhang et al (53) found that the expression of the lncrna loXl1-aS1 was high in the peripheral blood from patients with osteoporosis and that this gradually decreased during the process of osteogenic differentiation of hBMScs.…”
Section: Mechanisms By Which Ncrnas Regulate Bmscs In Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs have been found to participate in the pathogenesis related to PD by regulating neuroinflammation, oxidative stress ( Bu et al, 2020 ), cell cycle, mitochondrial dysfunction, and amyloid β (Aβ) production ( Chen Y. et al, 2019 ; Gao et al, 2020 ). In addition, lncRNA Xist regulates osteoblast differentiation by sponging miR-19a-3p in aging-induced osteoporosis of bone marrow mesenchymal stem cells ( Chen et al, 2020 ). A recent profiling study also showed that many lncRNAs were significantly altered in peripheral blood of depressed patients ( Cui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%